Islet NO-Synthases, extracellular NO and glucose-stimulated insulin secretion: Possible impact of neuronal NO-Synthase on the pentose phosphate pathway - Ingmar Lundquist; Israa Mohammed Al-Amily; Ragnar Henningsson; Albert Salehi (PLoS ONE, 2025)
The impact of islet neuronal nitric oxide synthase (nNOS) on glucose-stimulated insulin secretion (GSIS) is less understood. We investigated this issue by performing simultaneous measurements of the activity of nNOS versus inducible NOS (iNOS) in GSIS using isolated murine islets. Additionally, the significance of extracellular NO on GSIS was studied. Islets incubated at basal glucose showed modest nNOS but no iNOS activity. Glucose-induced concentration-response studies revealed an increase in both NOS activities in relation to secreted insulin. Culturing at high glucose increased both nNOS and iNOS activities inducing a marked decrease in GSIS in a following short-term incubation at high glucose. Culturing at half-maximal glucose showed strong iNOS expression revealed by fluorescence microscopy also in human islets. Experiments with nNOS-inhibitors revealed that GSIS was inversely related to nNOS activity, the effect of iNOS activity being negligible. The increased GSIS after blockade of nNOS was reversed by the intracellular NO-donor hydroxylamine. The enhancing effect on GSIS by nNOS inhibition was independent of membrane depolarization and most likely exerted in the pentose phosphate pathway (PPP). GSIS was markedly reduced, 50%, by glucose-6-phosphate dehydrogenase (G-6-PD) inhibition both in the absence and presence of nNOS inhibition. NO gas stimulated GSIS at low and inhibited at high NO concentrations. The stimulatory action was dependent on membrane thiol groups. In comparison, carbon monoxide (CO) exclusively potentiated GSIS. CO rather than NO stimulated islet cyclic GMP during GSIS. It is suggested that increased nNOS activity restrains GSIS, and that the alternative pathway along the PPP initially might involve as much as 50% of total GSIS. In the PPP, the acute insulin response is downregulated by a negative feedback effect executed by a marked upregulation of nNOS activity elicited from secreted insulin exciting insulin receptors at exocytotic sites of an nNOS-associated population of secretory granules.